(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction: Tuberculosis (TB) has been one of the health problems in the world. Diagnosis of pulmonary tuberculosis based on finding of AFB in the sputum has several limitations and mycobacterial culture is time consuming. So we decided to evaluate biomarker like Adenosine Deaminase (ADA) activity in Bronchoalvolar Lavage(BAL) fluid .Objectives: To study level of BAL ADA in sputum negative suspected cases of pulmonary tuberculosis and correlate it with BAL GenXpert (Cartridge Based Nucleic Acid Amplification) result. Method: We have enrolled suspected sputum negative pulmonary TB and suspected lung malignancy patients (as control). Total 33 patients - 17 suspected sputum negative pulmonary TB, 16 suspected lung malignancy were enrolled in study and subjected to bronchoscopy and BAL fluid was submitted for ADA level and GenXpert for TB. Result: Increased BAL ADA level was found in suspected sputum negative pulmonary TB as compare to suspected malignancy. Increased BAL level was well correlared with GenXpert positivity in suspected TB group. Conclusion: BAL fluid ADA can be useful tool for early diagnosis of suspected sputum negative pulmonary TB.